NAVOIY VILOYATI AHOLINING ISH BILAN BANDLIGINING HUDUDIY TAFOVUTLARI VA ULARNI RAYONLASHTIRISH - Norov, Sh.Sh. (SCIENCE and SOCIETY, 2025)
This article analyzes regional differences in the employment of the population of Navoi region and issues of their regionalization. The share and location of the regions in the employment of the population have been studied. Based on regionalization, this problem was analyzed into regions of irrigated farming, mountain and sub-mountain pasture livestock, and desert pasture livestock.